Strategies toward Green Deal implementation in the context of SCG reuse and recovery in the circular economy model - Jakub Drewnowski; Jun Xu; Hongyu Mao; Lurui Chen; Jacek Mąkinia; Joanna Szulżyk-Cieplak; Li Xie (Desalination and Water Treatment)
The article explores the future outlook on integrating and using a resource database for the recovery and reuse of coffee industry residues, focusing on economic and environmental perspectives within the Circular Economy Model (CEM). With the continuous rise in global coffee consumption, the production of Spent Coffee Grounds (SCG) has also surged worldwide, presenting significant opportunities for resource recovery and recycling. The reuse of SCG, a solid byproduct of coffee brewing, whether at home or on an industrial scale for soluble coffee production, is the subject of the article. This review aimed to consolidate existing knowledge on SCG output, management, characterization, treatment, and various methods for resource recovery and recycling to enhance understanding of SCG. Recent approaches include biodiesel production, biochar conversion, composting, co-digestion, extraction, as well as utilization in water treatment or construction. Despite these advancements, the SCG research community remains relatively small and disconnected, lacking timely exchange of information. Therefore, the development of high value-added products within the framework of Green Deal Implementation and CEM is strongly encouraged.